IMPLEMENTASI KEBIJAKAN DESTINASI PARIWISATA DI KELURAHAN PENYENGAT KECAMATAN TANJUNGPINANG KOTA - Pangestoeti, Wahyu (Jurnal Ilmu Administrasi Negara (JUAN), 2016)
IMPLEMENTASI KEBIJAKAN DESTINASI PARIWISATA DI KELURAHANPENYENGAT KECAMATAN TANJUNGPINANG KOTA Wahjoe Pangestoetiwpangestoeti@yahoo.com (Jurusan Ilmu Administrasi Negara FISIP UMRAH) Abstract The efforts of Tanjungpinang government in realizing Penyengat Island to be a tourist icon that puts the pilgrim tourist witha historical relics dan cultural heritage sites are very well known in the Province of Riau Archipelago at Region Regulation (Peraturan Daerah No. 8 Tahun 2010) about archaeological management, history, traditional value and Museum. The purpose of this research is to investigate the policy of implementation tourism destinations in Penyengat Island and to identify inhibiting factor while doing the policy implementation that have implementation that have implementation that have implemented in Penyengat Island tourism destinations.Based on that analyzes, researcher try to blow up how the tourism destination implementation that have implemented in Penynengat Island, Tanjungpinang district. The sample techniques used was purposive sampling. The reasech methode used a qualitative descriptive research that describing social phenomena without comparison and answer the hypothesis. The result of this research is the lack of implementation of Penyengat tourism destinations and lack of socialization in the government in issued a policy. The conclusions of this research can bee seen from the implementation indicators and the implementation of employee respondents who stated policy implementers tourism destination rarely attend trainning to improve knowledge in the tourism sector. The suggestion from this research is that the Tanjungpinang’s government can engage implementing tourism destination employees in Penyengat Island. Increased the monitoring of implementing tourism destination employees perfomance and give socialization to people so tourism destinations policy implementation can run as it should.